2021
DOI: 10.7150/ijms.59757
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of emergency medical technicians performing intermittent high-quality cardiopulmonary resuscitation

Abstract: Background: Whether intermittent chest compressions have an effect on the quality of CPR is worthy of discussion. The purpose of this study was to investigate differences in the chest compression quality of emergency medical technicians (EMTs) performing cardiopulmonary resuscitation (CPR) with different rest intervals. Methods: Seventy male firefighters with EMT licenses participated in this study. Participants completed body composition measurements and three CPR quality te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Previous studies [ 12 , 13 , 18 ] have found that body composition components are essential to understand the mechanism of resuscitation efforts. Our study exclusively focused on analyzing the differences between fat mass and specific fat-free mass components such as body water, muscle mass or body cell mass in relation to CPR parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [ 12 , 13 , 18 ] have found that body composition components are essential to understand the mechanism of resuscitation efforts. Our study exclusively focused on analyzing the differences between fat mass and specific fat-free mass components such as body water, muscle mass or body cell mass in relation to CPR parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 70 active firefighters, a significant positive correlation between the upper extremity muscle mass with the core muscle mass and chest compression depth was noted (r = 0.398, p = 0.001). A lack of significant correlations between the CPR quality and body fat percentage was also observed ( p > 0.05) [ 12 ]. It is worth mentioning that the results of the pilot study by Shin et al showed that FM% was significantly negatively correlated with the compression depth (r = −0.745, p = 0.001) and coexisted with non-significance for the skeletal muscles [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…시간에 따른 젖산 농도는 상승한다 (22) 혈중 젖산 농도는 시간 . 에 비례하여 증가하지 않지만 운동의 강도와 운동량에 따라 , 증가한다 (18) (19,28,29) 현재 현장에서는 최소 이상의 심폐 .…”
unclassified